Application of immunoblot assay for rapid diagnosis of human pythiosis - Jidapa Supabandhu (2018)
Objective: Pythiosis, a life-threatening infectious disease, has been reported from Maharaj Nakorn Chiang Mai hospital since 2001. Delayed diagnosis, due to difficulty in obtaining an appropriate specimen and in timely identification, causes delayed treatment resulting in a high mortality rate. To address this problem, a previously developed immunoblot has been evaluated and objected as an effective diagnostic tool for human pythiosis in this hospital. Material and Method: The immunoblot assay was evaluated using human sera with culturally proven fungal infection. Sera from humans with a variety of other fungal infections, pooled healthy human sera including Cryptococcus neoformans-, Penicillium marneffei-, and Histoplasma capsulatum-immunized rabbit antisera were used as controls. The assay was applied to evaluate twenty-six sera of suspected pythiosis patients. Moreover, in appropriate cases, a combination of immunoblot, culturing and polymerase chain reaction (PCR) were also performed in order to determine the accuracy of the immunoblot assay. Results: The presented immunoblot assay was not reactive with any sera of the controls or those of the other fungal-infected patients used in the present study. Pythiosis could be differentiated from other fungal infections with similar symptoms in sixteen of twenty-six samples of suspected patients. The positive ones showed the proper reactive pattern as shown in P. insidiosum-immunized rabbit serum. The present study provided evidence that the 40 to 35-kDa antigens were reactive specifically with all sera from both treated and active pythiosis patients. Culturing and PCR results were consistent with the immunoblot finding. Conclusion: The immunoblot assay developed in the present study is specific to P. insidiosum-infection and suitably applied as an effective tool for human pythiosis diagnosis.